(untitled) - TenBroek, Jacobus (Berkeley, 1954)
A must for any student of American history. This book provides historical details as well as thoughtful and well documented analysis of the political and administrative causes as well as the social causes of one of the darkest periods in the nation's history.
Keywords: Japanese americans,Civil rights; Evacuation and relocation, 1942-1945.; United states